Why the poor care about partial versus general equilibrium effects - Part I: methodology and country case - Wobst, Peter (International Food Policy Research Institute, 2000)
The paper compares the effects of productivity growth in agriculture in a standard CGE model and an adjusted CGE model with special features in order to replicate partial equilibrium behavior of traded agricultural sectors within a general equilibrium framework. The fixed-price, partial equilibrium CGE model shows a strong multiplier effect so that total GDP, factor earnings, and household incomes increase with the productivity growth in agriculture. In comparison, the standard CGE model generates much more diverse sectoral behavior, stronger trade through shifts in the exchange rate, and a less equitable income distribution among farm and non-farm households.